Financial projection analysis of a new logistic company design with rent and buy decisions - Brahmandyo Yudhowibowo, Yacobus; M. Daryanto, Wiwiek (The Indonesian Journal of Business Administration, 2019)
Abstract. Indonesia is the fourth biggest contry in the world with population of 263 Million people after China, India, and United States of America with many archipelagos. This fact made the population is not distributed normally. At least 57% of population live in Java, which is the center of government, education, and the wheel of economy. On the other side, the 87% of population are known to be Moslem made the needs of food and its distribution with Halal process is a must. Therefore, PT ABC which is a corporation that has enough experience in chain restaurants initiating to develop a business of Halal logistics. The goal of this study is to see the prospect of Halal logistic business in long term. To be a proper player in the industry, an initial project is done by making PT XYZ as a captive market of the new Halal logistic company. This study concentrates more on rent and buy method, capital and operating expenditure calculcation, and the profitability projection of the company for 10 years period to see the trend of the business in the point of view of financial management. From the study, it resulted that rent option is the best choice for the corporation to establish the new Halal logistic company since it provided lower capital expenditure, lower risk, and faster return on investment although the operating expenditure shows higher amount compared to buy option and less profitabilities.Keywords : Halal logistics, Profiabilities, Capital expenditures, Operating expenditures, Rent and Buy.